PENGARUH PENGGUNAAN PUPUK KANDANG AYAM DAN LUAS LAHAN GARAPAN TERHADAP HASIL PRODUKSI USAHATANI CABAI MERAH (Capsicum annum L) DI DESA DURIAASI KECAMATAN WONGGEDUKU KABUPATEN KONAWE - Kalis Amartani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This study aims to see the effect of chicken manure and the area of arable land on the production of red chili farming. This research was conducted in Desa Duriaasi Wonggeduku District of Konawe Regency with 35 respondents. The results showed that the use of chicken manure (X1) and the cultivated land area (X2) had an effect on the yield of red chili farming (Y) where the result of multiple linear regression analysis showed positive value to all observation variables while in partial t test and F test showed significant value <0,05 with coefficient of determination equal to 0,990 or 99,0%. Keywords: Poultry Poultry Manure, Area of Clogged Land, Production Result of Farming Red chili pepper.